MANAJEMEN RESIKO BISNIS UMKM STUDI PADA PRODUK USAHA NIKMAT BOBA - anggraAni, Depi; Awal Amarudin, Amin (ISTISMAR, 2019)
Abstrack: Small and medium enterprises or commonly known as SMEs also need to defend themselves from competition, besides that SMEs also need to face several world challenges, in facing global challenges, this can be done through product and service innovation, as well as developing human resources to realize and technical resources, as well as expanding the marketing area for MSMEs. Keyword : Business Risk Management, SMEs